A laterally coupled UV210 polymer racetrack micro-resonator for thermal tunability and glucose sensing capability. (3rd July 2015) - Castro-Beltrán, R.; Huby, N.; Vié, V.; Lhermite, H.; Camberlein, L.; Gaviot, E.; Bêche, B.
Abstract : Authors report and demonstrate the feasibility of a laterally coupled racetrack microresonator based on UV210 photoresist to act as a thermal and glucose sensor. The large thermo-optic coefficient and the detection principle based on the interaction of the evanescent field with different glucose concentrations demonstrate that this sensor displays high sensitivity on detection properties. Deep-UV lithography procedures allow us to develop a laterally coupled microresonator with submicrometer patterns. The thermo-optic response of the racetrack microresonator is interrogated by using a NiCr alloy tip positioned on the top of the device. Temperatures ranging between 19 and 33°C yield a red shift of the resonant wavelength with a linear sensitivity of 220 pm °C − 1 . Additionally, the thermal tunability is successively demonstrated by covering the resonator with DI water. A blue shift of the resonant wavelength is obtained with a linear sensitivity of 200 pm °C − 1 . The resonance optical properties under this top cladding conditions lead a Q-factor of 4000 with a finesse of 5.7. Glucose homogeneous sensing capability is also experimentally demonstrated. Different concentrations of glucose solutions result in a red shift of the resonant wavelengths with a linear sensitivity of 280 pm mg − 1  ml − 1 . Finally, these results validate the laterally coupled racetrack microresonator as an operative photonic component for integrated optical devices such as optical filters applied on telecommunication, or transducer components devoted to assess biochemical interactions. Graphical Abstract: